Tendencies of future music teachers’ attitude towards the assessment of the students’ progress and achievements under the conditions of the change of educational paradigms - Asta Kriščiūnaitė; Diana Strakšienė (Social Welfare: Interdisciplinary Approach, 2016)
The article deals with the topic that is especially relevant for the system of education of Lithuania that is undergoing the transformation of educational paradigms – assessment of students’ progress and achievements, which causes an especially great number of discussions in modern artistic/music education because of its specificity. The article focuses on the attitude of future music teachers towards the functions of the assessment of students’ progress and achievements, its impact on the microclimate of the educational process and having identified the relations of the assessment of students’ progress and achievements to the creation of pedagogical self-image it helped to understand what the tendencies of music education in Lithuania are and how they should be improved.